Speech actualization of ethophysiological targets of mass recipient manipulation in British political discourse - Lyulina, Anna V.; Yelagina, Yuliya S. (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2025)
Background. The political discourse is the type of discourse with exactly dominating manipulative intention. This intention has a complicated structure and is realized by the speech producer through actualizing of a definite set of mass recipient’s universal manipulation targets. With the help of the intentional analysis of the Conservative Party Manifesto the author proves that there is a special set of effective speech actualizers of mass recipient’s ethological and physiological manipulation targets being in a strict hierarchy. Purpose. The purpose of the study is to find out and analyze the speech means of actualizing of mass recipient’s ethological and physiological manipulation targets in the British political discourse. Materials and methods. This study is based on the recipient-centric approach with which mass recipient is regarded as some model of interdependent features being relevant for the process of manipulation and reflected on the surface level of producers’ manipulative messages in the system of speech means under consideration. Results. On the basis of the political party manifesto text type the intentional model of the manipulative speech act has been tested, as well as the recipient-centered model of manipulation targets for the mass recipient. It is proved that the most effective manipulation means of this text type are nominative actualizing signs and associative actualizing signs, which affect such manipulation targets as the anticipation of social ideal realization (in promissive speech acts), certain instincts, the interoception, exteroception and proprioception peculiarities and the characteristic features of temporal, space and kinetic perceiving as well. Обоснование. Политический дискурс является видом дискурса с ярко доминирующей манипулятивной интенцией. Данная интенция имеет сложную структуру и реализуется продуцентом с помощью речевой актуализации определенного набора универсальных мишеней манипуляции массовым реципиентом. С помощью интенционального анализа предвыборного манифеста Консервативной партии Великобритании автор доказывает, что существует определенный набор эффективных речевых актуализаторов этофизиологических мишеней манипуляции массовым реципиентом, находящихся в строгой иерархии. Цель – выявить и проанализировать речевые средства актуализации этофизиологических мишеней манипуляции массовым реципиентом в политическом дискурсе Великобритании. Материалы и методы. Данное исследование основано на реципиентоцентрическом подходе, при котором массовый реципиент рассматривается как модель его взаимодействующих характеристик, релевантных для процесса манипулирования и отраженных на поверхностном уровне фиксированных манипулятивных сообщений политиков-продуцентов в системе исследуемых средств. Результаты. На материале такого текстотипа как “манифест политической партии” апробирована интенциональная модель манипулятивного речевого акта, а также реципиентоцентрическая модель мишеней манипуляции массовым реципиентом. Доказано, что эффективными средствами манипуляции в данном текстотипе являются актуализаторы-ассоцианты и аткуализаторы-номинанты, воздействующие на такие мишени манипуляции массовым реципиентом, как ожидание осуществления социального идеала (промиссивные речевые акты), инстинкты, особенности экстерорецептивного, проприорецептивного и интерорецептивного восприятия, а также особенности темпорального, спациального и кинетического восприятия массового реципиента.